Fermentable Sugar Production and Separation from Water Hyacinth Using Enzymatic Hydrolysis - Khan, Maksudur R.; Saha, Pradip; Alam, Md. Fakhrul; Baishnab, Ajit Chandra; Islam, M. A. (Science and Education Publishing, 2014)
Water hyacinth containing a remarkable amount of cellulose which is found throughout the world as unusable material that can be used as one of the promising source for the production of glucose, initial step to produce bio ethanol. In this current study different types of treatments highest glucose concentration was obtained by hot water treated method. In addition, glucose was produced from water hyacinth using cellulytic enzyme pseudomonas sp., isolated from cow dung. Glucose concentration and production rate increases with the increasing of substrate concentration and enzyme loading, particle size 45µm and a pH 6.00 and temperature 40°C are the optimum for glucose production. A kinetic model rate expression has been developed for enzymatic hydrolysis of water hyacinth based on the Michaelis – Mentens model and parameters are determined. 0.15gm Reducing sugar are separated from the mixture of glucose water solution using 2 gm of water hyacinth. 0.531mg/l Cellulytic composition in water hyacinth are determined.